Drip Irrigation and Monitoring Based On Smart Irrigation - Thomas, Sanu Ann; Abraham, Neethan Elizabeth; Chandran, Reshma; Philip, Anu (International Journal of Computer Sciences and Engineering, 2025)
Water is an essential component for the development of plants in agriculture or irrigation. The paper stresses on the need of an externally hosted cloud computing platform to manage the database, android and the isolated server by the users across the country for irrigation. The system proposed in this paper uses information and communication technologies, allowing the user to consider and examine the information obtained by different sensors. Here we are using different sensors like humidity, temperature, moisture, light etc. These sensors give signal to the micro controller. Micro-controller gives the data to the isolated server through a serial communication. According to sensor values graph will be display on PC and Smart phone side and by using this graph user can on or off dripdevices. In this we keep threshold value for each sensor. The data is sent and processed on an isolated server, which stores the information from the sensors in a database, allowing further interpretation of data in a simple and flexible way. The intendedsystem may lead to enhance the farming practices, overcomingthe water crises and developing an upgraded agricultural systemforthecountry.